Effect of Three Bioenzymes on Compaction, Consistency Limits, and Strength Characteristics of a Sedimentary Residual Soil - Tanveer Ahmed Khan; Mohd Raihan Taha (Advances in Materials Science and Engineering)
Bioenzymes are organic degradable materials, currently introduced as soil improvement additives. In this experimental study, three types of bioenzymes from three different countries were used to improve Universiti Kebangsaan Malaysia (UKM) soil. UKM soil has properties quite similar to soils recommended as suitable by bioenzyme suppliers. The effect of the three bioenzymes on Atterberg limits, compaction characteristics, and unconfined compressive strength was studied. Controlled untreated and treated samples for two dosages at curing times up to three months were prepared and tested after completion of the curing period. Some results showed little improvement in compaction characteristics, and unconfined compressive strength, but no notable improvement was noticed in Atterberg limits. X-ray diffraction (XRD), X-ray fluorescence (XRF), and field emission scanning electron microscopy (FESEM) tests were conducted for untreated and treated soil samples after two months of curing. XRD and XRF did not show any change in mineralogy and chemical composition between controlled untreated samples and samples treated with the three bioenzymes. However, the FESEM images revealed a denser packing of particles for soil samples treated with two of the bioenzymes.